Marketing Strategy Development for Bezta Food Co. - Prasetya, Bayu Adhika; Taufik, Tonton (The Indonesian Journal of Business Administration, 2015)
Abstract. The potential of food and beverage industry in Indonesia is increasing, with a large population and continue to grow, plus the fact that Indonesian second highest expenditure are to purchase food and beverage product. This sector is expected to increase 5.2% growth per year. (The Archipelago Economy). One of its cause is the new wave of consuming class in Indonesia that contribute the economy growth. With more than 250 million population, Indonesia has the most promising market for food and beverage industry. By the data in GAPPMI, the demand increased by 91% from the period 2007 to 2013, and reached 770 trillion in 2013. Bezta Food Co. is a manufacturer of snack product that has a vision to become a famous snack company in Indonesia. Bezta Food Co. established in June 2014 in Semarang. The first product of the company is wolu chips that has a various flavors. As a new startup, Bezta Food Co. faced a problem that is low of brand awareness. Poor marketing strategy plan are the reason why Bezta Food Co. has low brand awareness. This affected to slow growth for the company. The company should solve the problem by implementing marketing strategy to increase the brand awareness. First step is by scanning the external environment to understand the external condition that affect the company, such as societal environment, task environment, and competitors. The second step is by scanning the internal environment of the company to figure out about company product, service, and how the company operated. Based on the external environment and internal environment analysis, the proposed marketing strategy development is divided into two priority. The first priority is to improve product packaging to compete with other competitors. The second priority is to maximize the brand promotion through internet tools. To solve the problem is required a concrete steps that explained in the implantation plan. Keywords: Food and beverage industry, snack products, brand awareness, marketing strategy.